Fatal outcome of anaphylaxis - triggers, cofactors, management, prevention and forensic aspects - Maciej Kycler; Szymon Rzepczyk; Paweł Świderski (Śląski Uniwersytet Medyczny w Katowicach, 2024)
Anaphylaxis is a life-threatening condition characterized by a rapid onset, requiring immediate intervention. It occurs through immunologic or non-immunologic mechanisms and can be triggered by various factors such as foods, medications or insect venoms. The spectrum of symptoms is broad, with skin, respiratory, and gastrointestinal symptoms being most commonly observed. Diagnosis relies on clinical criteria, with the primary treatment involving the intramuscular administration of adrenaline. Prevention involves avoiding triggers and if avoidance is not possible, desensitization should be considered. Deaths from anaphylactic shock are rare and often result from delayed or improper medical assistance and the absence of witnesses to summon help. It is estimated that around 1% of anaphylactic shock cases result in death. Deaths from intentional attempts to induce anaphylactic reactions through suicide are rare. Postmortem diagnosis presents a challenge due to the lack of specific changes, therefore it is essential to thoroughly assess the circumstances of death, medical history and exclude other potential causes. Identifying factors that may trigger an anaphylactic reaction, such as ingested foods or contact with allergens is crucial. A rapid and accurate diagnosis is key to avoid errors resulting from post-mortem processes. Histopathological examinations and the measurement of biochemical markers, such as tryptase and IgE levels, may be helpful in determining the cause of death.